MARKET ORIENTATION AND ENVIRONMENTAL PRODUCT INNOVATION ON BUSINESS PERFORMANCE : THE MEDIATING ROLE OF COMPETITIVE ADVANTAGE - Sandy Hana Widya Sims; Bima Cinintya Pratama; Iwan Fakhruddin; Nur Isna Inayati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to analyze the effect of market orientation and environmental product innovation on business performance in MSMEs, with competitive advantage as a mediating variable. Market orientation is a factor that allows MSMEs to survive and thrive in increasingly fierce competition. In addition, environmentally based product innovation focuses on developing environmentally friendly products. This research uses a quantitative method with a survey approach to a number of MSME actors. The targets of this research were MSME actors in Banjarnegara, Purbalingga, Banyumas, Cilacap and Kebumen Regencies. The data used uses primary data and used a sample of 200 respondents. The analytical tool used in this research is Smart-PLS by using the inner model, outer model, and hypothesis testing. Outer model is used for validity and reliability tests. Inner model is used for R-square and F-square tests and hypothesis testing using Bootstrapping testing. The results of this study indicate that the variables of Market Orientation, Environmental Product Innovation, and Competitive Advantage have a positive effect on Business Performance. The practical implication of this study is that MSMEs must pay attention to and optimize business potential by considering Market Orientation, Environmental Product Innovation, Competitive Advantage to improve business performance. Keywords: Business performance, Competitive advantage, Environmental product innovation, Market Orientation.